Price Risk Management effect on the China’s Egg "Insurance + Futures" Mode : an empirical analysis based on the AR-Net model: 10.48129/kjs.splml.19407 - LIU, Chen; Yuhe, ZHAO (Kuwait Journal of Science, 2022)
Stable egg prices in China are related to people's livelihood, and layer farmers are facing the risk of large fluctuations in egg prices. This paper verifies that the AR-Net model can predict egg futures prices better than neural network model or other universal statistical models. Based on this result, the AR-Net model is also used to determine the insurance price and premium rates, further to evaluate price risk management effect of the "insurance + futures" mode. On this basis, we obtained several important conclusions: (1) Compared to other price prediction methods, AR-Net model is more suitable for egg futures price prediction in China. (2) China’s egg "insurance +futures" mode can conducive to stabilizing the income of layer farmers. (3) "Insurance + Futures" mode can exert better risk management results compared with traditional "insurance + futures" mode and agricultural price insurance.